Improving adolescent knowledge on early marriage through school-based education - Agustin, Dian Triana; Hidayat, Unang Arifin; Suptiani, Laila Putri (Jurnal Kesehatan Ibu dan Anak, 2025)
Early marriage remains a prevalent issue in Indonesia, particularly in rural areas such as Cibalong District, Tasikmalaya. Despite national efforts, the lack of structured, school-based reproductive health education contributes to persistent high rates of underage marriage. This study aims to evaluate the effectiveness of educational intervention on adolescents’ knowledge regarding early marriage. A pre-experimental study using a one-group pretest-posttest design was conducted from October to November 2024 at SMPN 1 Cibalong, Tasikmalaya, Indonesia. A total of 132 Grade IX students were selected using purposive sampling. The intervention consisted of a 60-minute school-based educational session focusing on the definition, causes, risks, impacts, and prevention of early marriage, delivered through multimedia presentations and group discussion. Knowledge was assessed using a validated 20-item questionnaire before and one week after the intervention. Data were analyzed using Wilcoxon signed-rank test with a significance level of p < 0.05. Prior to the intervention, 38.64% of students had low knowledge levels, 29.55% moderate, and 31.82% high. Post-intervention, 87.12% had high knowledge, 12.88% moderate, and none remained in the low category. Statistically significant improvements were observed across all six indicators of early marriage knowledge, including understanding, causes, risk, prevention, impact, and contributing factors (p = 0.000). The findings confirm that targeted, school-based reproductive health education effectively improves adolescents’ knowledge and awareness about early marriage. This low-cost, scalable approach can be integrated into school curricula and may serve as a preventive strategy against early marriage in high-risk areas.